2019
DOI: 10.1021/acsapm.9b00061
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Reactive Compatibilization of PLLA/PVDF Blends Investigated by Scanning Transmission Electron Microscopy with Energy-Dispersive X-ray Spectrometry and Electron Energy Loss Spectroscopy

Abstract: The localization of reactive compatibilizers at the interfaces in polymer blends of PLLA (poly(L-lactic acid)) and PVDF (poly(vinylidene fluoride)) was investigated by scanning transmission electron microscopy (STEM) combined with energy-dispersive X-ray spectrometry (EDX) and electron energy loss spectroscopy (EELS). Polyhedral oligomeric silsesquioxane (POSS) functionalized with epoxide groups and poly(methyl methacrylate) (PMMA) chains was applied as compatibilizer in the immiscible PLLA/PVDF (50/ 50 wt %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The bright yellow region in the AFM image indicated PVDF, and the dark yellow region indicated the cavity caused by the elimination of PMMA, as shown in Figure 4 . The morphology revealed that the distribution of PVDF and PMMA was ultra-fine (∼μm) across the entire range of ratio, illustrating highly homogenous dispersion caused by in situ polymerization ( Kang et al, 2009 ; Dong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The bright yellow region in the AFM image indicated PVDF, and the dark yellow region indicated the cavity caused by the elimination of PMMA, as shown in Figure 4 . The morphology revealed that the distribution of PVDF and PMMA was ultra-fine (∼μm) across the entire range of ratio, illustrating highly homogenous dispersion caused by in situ polymerization ( Kang et al, 2009 ; Dong et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PPS/Al5052 interfacial structures were investigated by electron microscopy using a TECNAI Osiris (FEI company, USA) scanning transmission electron microscope (STEM) with an accelerating voltage of 200 kV. Energydispersive X-ray (EDX) microanalysis and STEM/EDX elemental mapping were performed with 4 windowless silicon drift EDX detectors (Super-XTM), which were placed symmetrically around the optical axis near the specimen area [5]. STEM-tomography was performed to construct detailed 3D structures of the joint interface [6], where series of STEM images by sequentially tilting a specimen in the tilt range of ±60 degrees.…”
Section: Characterization Of the Joint Interfacesmentioning
confidence: 99%
“…STEM‐EDX is another technique that can be used for elemental mapping. Scanning the electron beam over a 2D region of a specimen gives a quick overview of the elements present and their spatial distribution 27 . In conventional STEM‐EDX systems, X‐rays emitted from the specimen are detected by a single detector located diagonally above the specimen.…”
Section: Introductionmentioning
confidence: 99%